2004
DOI: 10.1128/jb.186.13.4192-4198.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dps Protects Cells against Multiple Stresses during Stationary Phase

Abstract: Dps, the nonspecific DNA-binding protein from starved cells, is the most abundant protein in stationaryphase Escherichia coli. Dps homologs are found throughout the bacteria and in at least one archaeal species. Dps has been shown to protect cells from oxidative stress during exponential-phase growth. During stationary phase, Dps organizes the chromosome into a highly ordered, stable nucleoprotein complex called the biocrystal. We show here that Dps is required for long-term stationary-phase viability under co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
292
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(301 citation statements)
references
References 32 publications
(46 reference statements)
6
292
2
1
Order By: Relevance
“…Whereas this putative metal-binding motif is distinct from that (47). Whereas dps expression is generally considered specific to oxidative stress during exponential growth, Dps proteins have been shown to effectively protect against a broad spectrum of different stresses while in stationary phase (48). SsDps is also likely to confer protection against a broader range of environmental stress during stationary phase; however, growth of S. solfataricus is limited by the accumulation of inorganic ions and thus complicates studies aimed at understanding S. solfataricus physiologies under true nutrient limitation (49).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas this putative metal-binding motif is distinct from that (47). Whereas dps expression is generally considered specific to oxidative stress during exponential growth, Dps proteins have been shown to effectively protect against a broad spectrum of different stresses while in stationary phase (48). SsDps is also likely to confer protection against a broader range of environmental stress during stationary phase; however, growth of S. solfataricus is limited by the accumulation of inorganic ions and thus complicates studies aimed at understanding S. solfataricus physiologies under true nutrient limitation (49).…”
Section: Discussionmentioning
confidence: 99%
“…Dps was initially identified as a protein that coats DNA in vitro, and subsequent electron microscopy studies have indicated that it does so in vivo in stationary-phase bacteria (43,44). This behavior was rationalized on the grounds that by coating the DNA, the protein would protect it from chemical damage, including oxidants.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli Dps, first characterized as an antioxidant protein, was abundantly expressed during the stationary phase in response to nutrient stress or oxidative stress (10). It was shown to incorporate DNA without sequence specificity and further exert protection against hydrogen peroxide stress, Dnase cleavage, UV radiation and acid shock (10,11). Based on sequence analysis, Dps are endowed with conserved ferroxidase domain, implicating that they also belong to ferritin family.…”
Section: Introductionmentioning
confidence: 99%
“…In E. coli, the structure, biochemical characterization and cellular regulation of Dps protein have been extensively investigated (5 -9). E. coli Dps, first characterized as an antioxidant protein, was abundantly expressed during the stationary phase in response to nutrient stress or oxidative stress (10). It was shown to incorporate DNA without sequence specificity and further exert protection against hydrogen peroxide stress, Dnase cleavage, UV radiation and acid shock (10,11).…”
Section: Introductionmentioning
confidence: 99%